ISLAM: AGAMA ANTI KEKERASAN - Yuwono, Yohanes H. (LOGOS - Jurnal Filsafat Teologi, 2002)
No single of the revealed religions nor Islam, encourages or teaches violence to its believers. Islam which is based on the Qurâan as its Holy Scripture summons its faithfuls to spread peace, harmony and social welfare. It is true that we find several verses that encourage war, but jihad in the sense of holy war in Islam is the last way of a self defense after all good manner of dialogs fail to bear fruits of understanding. In these sense jihad could be done because the truth must stand firm before evil.